Supply Chain Coordination with Flexible Payment Policy under Effect of Green Technology Investments - Shah, Nita H.; Shah, Pratik; Patel, Milan (Yugoslav Journal of Operations Research; Vol 33 No 3 (2023)DO - 10.2298/YJOR220616029S, 2022)
At present, augmentation of carbon gases in atmosphere has become a major concern. Regulatory bodies in many countries have focused on reduction of carbon emissions. Several countries follow carbon tax and carbon cap trade policy to control emission of carbon gases. This study has been carried out to obtain joint inventory policies for a supply chain involving a manufacturer and a whole-seller. Moreover, the manufacturer invests in green technology to reduce units of carbon gases. Products are considered deteriorating in nature. Manufacturer delivers product by adopting a lot-for-lot policy to meet the whole-seller’s demand. The manufacturer offers the whole-seller flexible payment options including advance payment with discounted product price and delayed payment with increment in product price. Optimal policies for both individuals and the supply chain are discussed with aim to maximize total profit. The model is worked out and results are compared for four cases: (i) advance payment with green technology investments (ii) advance payment without green technology investments (iii) delayed payment with green technology investments (iv) delayed payment without green technology investments. A solution procedure has been proposed and explained through a numerical example. Study is concluded with managerial insights.